-1 1/6 x 7

3 answers

-1 1/6 x 7 can be computed as follows:

First, convert the mixed number -1 1/6 to an improper fraction:
-1 1/6 = -6/6 + 1/6 = -7/6

Now, multiply -7/6 by 7:
-7/6 x 7 = -49/6

Therefore, -1 1/6 x 7 is equal to -49/6.
What is it in mix number
To convert -49/6 to a mixed number, divide the numerator (-49) by the denominator (6):

-49 รท 6 = -8 remainder 1

The quotient (whole number part) is -8, and the remainder is 1. This can be expressed as a mixed number:

-1 1/6

Therefore, -49/6 is equal to -1 1/6 as a mixed number.